Stripping voltammetric methods for the determination of aflatoxin compounds - Yaacob, Mohamad Hadzri (2006)
Aflatoxin, which is produced by Aspergillus flavus and Aspergillus parasiticus fungi is one of the compounds in the mycotoxin group. The main types of aflatoxins are AFB1, AFB2, AFG1 and AFG2 which have carcinogenic properties and are dangerous to human health. Various techniques have been used for their measurements such as the high performance liquid chromatography (HPLC), enzyme linked immunosorbant assay (ELISA) and radioimmunoassay (RIA) but all these methods have disadvantages such as long analysis time, consume a lot of reagents and expensive. To overcome these problems, the voltammetric technique was proposed in this study using controlled growth mercury drop (CGME) as the working electrode and Britton Robinson buffer (BRB) as the supporting electrolyte. The voltammetric methods were used for investigating the electrochemical properties and the quantitative analysis of aflatoxins at the mercury electrode. The experimental conditions were optimised to obtain the best characterised peak in terms of peak height with analytical validation of the methods for each aflatoxin. The proposed methods were applied for the analysis of aflatoxins in groundnut samples and the results were compared with those obtained by the HPLC technique. All aflatoxins were found to adsorb and undergo irreversible reduction reaction at the working mercury electrode. The optimum experimental parameters for the differential pulse cathodic stripping voltammetry (DPCSV) method were the BRB at pH 9.0 as the supporting electrolyte, initial potential (Ei): -0.1 V, final potential (Ef): -1.4 V, accumulation potential (Eacc): - 0.6 V, accumulation time (tacc): 80 s, scan rate: 50 mV/s and pulse amplitude: 80 mV. The optimum parameters for the square wave stripping voltammetry (SWSV) method were Ei = -0.1 V, Ef = -1.4 V, Eacc: -0.8 V, tacc: 100 s, scan rate: 3750 mV/s, frequency: 125 Hz and voltage step: 30 V. At the concentration of 0.10 ÂµM, using DPCSV method with the optimum parameters, AFB1, AFB2, AFG1 and AFG2 produced a single peak at -1.21 V, -1.23 V, -1.17 V and -1.15 V (versus Ag/AgCl) respectively. Using the SWSV method, a single peak appeared at -1.30 V for AFB1 and AFB2 while -1.22 V for AFG1 and AFG2. The calibration curves for all aflatoxins were linear with the limit of detection (LOD) of approximately 2.0 ppb and 0.50 ppb obtained by the DPCSV and SWSV methods respectively. The results of aflatoxins content in individual groundnut samples do not vary significantly when compared with those obtained by the HPLC technique. Finally, it can be concluded that both proposed methods which are accurate, precise, robust, rugged, fast and low cost were successfully developed and are potential alternative methods for routine analysis of aflatoxins in groundnut samples